Critical Discourse Analysis of “Criticism of the Representation of Islam in Western Media and the Role of Da’wah in Transformation” by Suud Sarim Karimullah - Rahman, Fathan Tibyan; Sajidin , Sajidin (UIN Sunan Gunung Djati Bandung, 2026)
This study critically analyzes Suud Sarim Karimullah's article,